Copper‐Catalyzed Cross‐Coupling of Secondary α‐Haloamides with Terminal Alkynes: Access to Diverse 2, 3‐Allenamides. Issue 7 (13th February 2018) - Lv, Yunhe; Pu, Weiya; Zhu, Xueli; Zhao, Tiantian; Lin, Feifei
Abstract: A copper‐catalyzed C( sp )−C( sp 3 ) cross‐coupling of terminal alkynes with readily available secondary α‐haloamides for the efficient synthesis of 2, 3‐allenamides is realized. The methodology is characterized by its wide substrate scope, which makes it an important complement to traditional methods for synthesizing allenes. A mechanism involving an alkynylcopper species is proposed. Abstract :